2003
DOI: 10.1111/j.0022-3506.2004.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Costs of Parents' Conditional Regard: A Self‐Determination Theory Analysis

Abstract: Parents' use of conditional regard as a socializing practice was hypothesized to predict their children's introjected internalization (indexed by a sense of internal compulsion), resentment toward parents, and ill-being. In Study 1, involving three generations, mothers' reports of their parents' having used conditional regard to promote academic achievement predicted (a) the mothers' poor well-being and controlling parenting attitudes, and (b) their college-aged daughters' viewing them as having used condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
490
2
22

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 436 publications
(567 citation statements)
references
References 74 publications
28
490
2
22
Order By: Relevance
“…Given the predominance of interest in violent game content, it is noteworthy that little research to date has examined how game structure might also shape short-term shifts in aggression through motivational processes. Past SDT research has shown that motivational processes based on psychological need deprivation can lead to more aggressive behavior in real-world contexts (Assor, Roth, & Deci, 2004;Ryan & Grolnick, 1986). Related research indicates that interfering with performance in goal pursuit, even in trivial tasks, can elicit heightened aggression (Berkowitz, 1989;Pedersen, Gonzales, & Miller, 2000).…”
Section: Sources Of Player Aggressionmentioning
confidence: 99%
“…Given the predominance of interest in violent game content, it is noteworthy that little research to date has examined how game structure might also shape short-term shifts in aggression through motivational processes. Past SDT research has shown that motivational processes based on psychological need deprivation can lead to more aggressive behavior in real-world contexts (Assor, Roth, & Deci, 2004;Ryan & Grolnick, 1986). Related research indicates that interfering with performance in goal pursuit, even in trivial tasks, can elicit heightened aggression (Berkowitz, 1989;Pedersen, Gonzales, & Miller, 2000).…”
Section: Sources Of Player Aggressionmentioning
confidence: 99%
“…En revanche, ceux qui bénéficient d'un soutien inconditionnel se sentent encouragés et aimés pour ce qu'ils sont comme personne et non pour ce qu'ils font. Concrètement, les parents offrant un soutien conditionnel démontrent plus de chaleur et d'affection lorsque l'enfant se comporte ainsi qu'ils le souhaitent et en démontrent moins lorsqu'il ne se comporte pas comme attendu (Assor, Roth et Deci, 2004). Le soutien conditionnel offert est propre à différents domaines, par exemple le domaine scolaire.…”
Section: Anxiété D'évaluationunclassified
“…Le soutien conditionnel offert est propre à différents domaines, par exemple le domaine scolaire. Selon la théorie de l'autodétermination (Assor, Roth et Deci, 2004;Deci et Ryan, 1985, la perception de l'élève que le soutien de ses parents est conditionnel à sa performance scolaire mène à la régulation introjectée. Par conséquent, l'élève intériorise les contraintes parentales et ressent de la culpabilité lorsqu'il n'agit pas de la façon attendue.…”
Section: Anxiété D'évaluationunclassified
See 1 more Smart Citation
“…Further, Assor, Roth and Deci (2004) showed that one type of controlling parenting, namely the use of conditional regard, promoted internal compulsion to Need Frustration and Vulnerability 20 engage in the parent-requested behaviors, and lowered wellness.…”
mentioning
confidence: 99%